2019
DOI: 10.18280/ijht.370302
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Investigation on a Caloric Heat Pump Employing Nanofluids

Abstract: Nowadays vapor compression is still the reference technique for heat pumping applications. There are Not-In-Kind heat pumping technologies where a prominent role is occupied by the ones based on solid-state refrigerants, called caloric. The name of such class of technologies comes from caloric effect, manifesting in caloric materials as temperature change due to an applied external field which changes its intensity adiabatically. The reference thermodynamical cycle is called Active Caloric Regenerative heat pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…[93,94] In 2019, they completed the study by analyzing the influence of novel heat transfer fluids such as Al 2 O 3 -water nanofluids. [95] The authors concluded that with this kind of fluids the caloric coolers could notably improve their performance.…”
Section: Fluid-based Ec Modelsmentioning
confidence: 99%
“…[93,94] In 2019, they completed the study by analyzing the influence of novel heat transfer fluids such as Al 2 O 3 -water nanofluids. [95] The authors concluded that with this kind of fluids the caloric coolers could notably improve their performance.…”
Section: Fluid-based Ec Modelsmentioning
confidence: 99%
“…Note that there are some models that claim to be general, that is, can be used for all caloric types, and are validated experimentally. However, the validation is not performed for all the caloric mechanism types 4,171,172 …”
Section: Numerical Implementationmentioning
confidence: 99%